The given function is
f(x)= log 10 x
Taking base as 10
→→Using the property of, log a b= log a + log b
→y = 1 + as,
we have to approximate the value of y in the equation
→10 y = 6
→y=
= 1 +
=
x= ==0.398
Solving graphically,
we get , x= 0.398 for , y= =.6
property
Answer:
-3n-+21
Step-by-step explanation: 1. Get rid of the Parenthesis , so times -3 by what’s inside
2. If you multiply -3 by n you get -3n
3. if you multiply -3 by -7 you get 21 , you get a positive because a negative times a negative is a positive
4. so now you have -3n + 21 you don’t add these because -3n has a variable and 21 doesn’t have a variable , and if 21 did have a variable it would need to also be n
Answer:
−3n + 21
Step-by-step explanation:
This is the answer because:
1) You have to distribute everything from outside of the parenthesis to the inside
2) -3 times n is -3n
3) -3 times -7 is 21
4) Therefore, the answer is −3n + 21
Hope this helps!
B. csc right triangle C right triangle equals fraction 3 over 2
C. csc right triangle B right triangle equals fraction 6 over 5
D. csc right triangle C right triangle equals fraction 5 over 6
Can you send a picture of the triangle. Maybe take a screen shot?
The distance of the run is 13.125 miles. The total time for the slower jogger was found to be 2.625 hours. Thus, both joggers ran the same distance, but at different speeds resulting in different finish times.
The problem deals with the concept of relative speed in mathematics. To find the distance of the run, we first need to figure out the time it took for each jogger to finish the run. We know that the slower jogger finished 45 minutes after the faster one. Since the speed equivalence is expressed in miles per hour (mph), let's convert 45 minutes into hours by dividing 45 by 60, giving us 0.75 hours.
Given that the slower jogger runs at 5 mph, and they took 0.75 hours longer than the faster one, we know they ran for a certain time 't', so we can represent this as t = total time of slower jogger's run.
The faster jogger ran at 7 mph. Since the jogger was 0.75 hours ahead of the slower one, the time would be represented by t - 0.75 hours = total time of faster jogger's run. The distance travelled by each jogger is 'speed x time'.
Following this, we equal these distances because it's the same course: 5t = 7(t - 0.75).
Solving this equation gives us t = 2.625 hours (total time for slower jogger). To find the run's distance, we can now substitute total time into either jogger's speed x time calculation. We'll use the slower jogger here: Distance = 5t = 5*2.625 = 13.125 miles.
#SPJ3
hyperbola
parabola
circle